(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
According to the cognitive model, anxious people allocate their attentional resources for threatening stimuli, staying in permanent surveillance state and concern. This supposition was tested through the performance in the Stroop tasks. In the Experiment 1, 60 students, divided in function of the anxiety degree, executed the classic and emotional Stroop tasks. The results show that the time to name colors of threatening words increases with the anxiety. In the Experiment 2 it was investigated if concrete or abstract words have different effects on the performance in the Stroop task. The results show that the time to name colors of concrete words (threatening or not) is larger than for abstract words. The results confirm the supposition above, specially for concrete threatening words and suggest the importance of the semantic quality of the stimuli in the Stroop task.